Are Nonfinancial Measures Leading Indicators of Financial Performance? An Analysis of Customer Satisfaction - Ittner, Christopher D.; Larcker, David F. (Journal of Accounting Research, 1998)
Christopher D. Ittner, David F. Larcker, Are Nonfinancial Measures Leading Indicators of Financial Performance? An Analysis of Customer Satisfaction, Journal of Accounting Research, Vol. 36, Studies on Enhancing the Financial Reporting Model (1998), pp. 1-35